2009
DOI: 10.1136/ard.2009.118067
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the experience of fatigue among patients with rheumatoid arthritis: a qualitative study

Abstract: Results point to the existence of differences in fatigue experience according to gender, age and daily roles. This finding indicates a need for targeting advice and interventions to the individual situation of a patient. Furthermore, the positive aspects patients reported about their fatigue could facilitate an approach that is focused on remaining opportunities and not just on restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 16 publications
5
73
2
Order By: Relevance
“…In FM, it appeared that there was a diurnal relationship between pain and fatigue that probably was mediated by stress or sleep quality (31,32). It may be worthwhile to evaluate sex differences; for example, it has been found that especially younger women with multiple daily roles seemed to be vulnerable to the negative impact of RA fatigue (33). However, in our study, no difference between men and women was found.…”
Section: Discussioncontrasting
confidence: 54%
“…In FM, it appeared that there was a diurnal relationship between pain and fatigue that probably was mediated by stress or sleep quality (31,32). It may be worthwhile to evaluate sex differences; for example, it has been found that especially younger women with multiple daily roles seemed to be vulnerable to the negative impact of RA fatigue (33). However, in our study, no difference between men and women was found.…”
Section: Discussioncontrasting
confidence: 54%
“…It was reported that experience of fatigue varies with respect to age, sex, emotions, and daily roles. Nikolous et al 40 showed that effects and experiences of fatigue vary individually. Particularly, young females with multiple daily roles have greater tendency to experience negative effects of fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…However, this domain is considered an important issue in other rheumatic diseases; several qualitative studies (107,108) have pointed out the importance of fatigue for patients with RA. In RA, fatigue is considered intrusive and overwhelming and has consequences on all aspects of quality of life (107,108). In PsA, however, there is a lack of data regarding the importance of fatigue for patients.…”
Section: Discussionmentioning
confidence: 99%